Co-digestion of Sorghum Stalk and Sludge for Biogas Production - Romli, Muhammad; Anggraini, Aulia; Purwoko,; Suprihatin, (Makara Journal of Science, 2015)
The recycling of residual agricultural biomass using anaerobic digestion allows for the recovery of biomass carbon and nutrients as sources of energy and fertilizer. The obstacles that are encountered in this process include the lignocellulosic structure of biomass tissue and its high carbon-to-nitrogen (C:N) ratio. This study evaluates the co-digestion system of pretreated sorghum stalks and wastewater sludge. The stalks were pretreated by partial bio-oxidation to improve their bacterial accessibility. The digesters were fed a mixture of stalk and sludge at ratios of 100:0, 80:20, 60:40, and 40:60 (total solids [TS] basis). The digesters were run in batches at 35-36 °C, with an initial TS of 15%. The digesters’ performance was evaluated in terms of biogas production rate and yield. The digesters that were run with feed ratios of 80:20 and 60:40 showed shorter lag phase, higher biogas generation rates, and higher biogas yields compared to those run with feed ratios of 100:0 and 40:60. The highest specific biogas production (of 122 L/kg TS) was achieved by the digesters run at ratios of 80:20 and 60:40. The digesters run only with stalks (ratio 100:0) resulted in specific gas production of 67 L/kg TS, whereas those fed on a feed ratio of 40:60 generated only 13 L/kg TS. We conclude that the co-digestion of sorghum stalks and wastewater sludge at a proper ratio improves biogas production.